Legal Status of Wasteland and Government Control and Use of Wasteland - Yani, Ahmad (International Journal Labs, 2023)
Background: Abandonment of land is an act that is unwise, uneconomical, unfair, and also a violation of the obligations that must be carried out by the right holders. The problem of abandoned land is one of the problems that needs to be quickly addressed in the land sector because it has many negative impacts. Aim: This study aims to analyze the Legal Position of Abandoned Land Based on the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 20 of 2021 and the Control and Utilization of Abandoned Land by the Government. Method: The normative juridical research approach was adopted for this study. The researcher examined legal sources, including books, journals, and laws, that dealt with the legal issue of wasteland. The descriptive qualitative technique was then used by the researcher to analyze them. Findings: After the evaluation results come out and declare the land identified as abandoned, the Head of the Regional Office will give a warning to the rights holder. If after the third warning is given but the right holder still does not comply with the warning, the Head of the Regional Office may propose to the Head of the Agency to designate the land as wasteland.